2009
DOI: 10.1248/yakushi.129.749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Simulations for Dosage Optimization of Docetaxel in Patients with Liver Dysfunction, Based on a Log-binominal Regression for Febrile Neutropenia

Abstract: This study was aimed to perform clinical trial simulations to evaluate the dose reduction strategy of docetaxel for Japanese patients with liver dysfunction, which we previously proposed. For this purpose, a log-binominal regression (LBR) was performed for febrile neutropenia (FN) induced by docetaxel in these patients. A LBR analysis was conducted using clinical data from cancer patients treated with docetaxel and incorporated in the subsequent trial simulation. Virtual patients with liver dysfunction were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has been reported that an average of 37% of obese patients undergoing bariatric surgery have NASH, which is higher than the rate observed in the general US adult population (Lazo and Clark, 2008). For both morphine and docetaxel, hepatic dysfunction is well documented to alter PK and requires dose-adjustment to avoid the occurrence of ADRs, potentially due to alteration in hepatic metabolism and transporter function (Bruno et al, 2001; Eckmann et al, 2014; Hasselström et al, 1990; Linares et al, 2009; Ozawa et al, 2008, 2009; Yoon et al, 2012). For docetaxel, several studies have attempted to assess whether doses should be adjusted based on various measures of obesity and body surface area (Griggs et al, 2012; Rudek et al, 2004; Sparreboom et al, 2007).…”
Section: Why Is Nash Currently Not Identified As a Key Player In Imentioning
confidence: 99%
“…It has been reported that an average of 37% of obese patients undergoing bariatric surgery have NASH, which is higher than the rate observed in the general US adult population (Lazo and Clark, 2008). For both morphine and docetaxel, hepatic dysfunction is well documented to alter PK and requires dose-adjustment to avoid the occurrence of ADRs, potentially due to alteration in hepatic metabolism and transporter function (Bruno et al, 2001; Eckmann et al, 2014; Hasselström et al, 1990; Linares et al, 2009; Ozawa et al, 2008, 2009; Yoon et al, 2012). For docetaxel, several studies have attempted to assess whether doses should be adjusted based on various measures of obesity and body surface area (Griggs et al, 2012; Rudek et al, 2004; Sparreboom et al, 2007).…”
Section: Why Is Nash Currently Not Identified As a Key Player In Imentioning
confidence: 99%
“…22,23 In the current assessment, the structural PK model parameters and associated variability estimates were used to simulate plasma concentration vs time profiles in 1000 hypothetical subjects at each of the following doses: 800 mg BID, 1200 mg BID, 1600 mg BID, and 1200 mg 3 times daily (TID). The estimated mean parameters and variability estimates from the modeled data were used in Trial Simulator (version 2.2; Certara, Princeton, New Jersey) for dose selection and justification in a (separate) 3-day PoC study in HCV patients.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…The Trial Simulator uses Monte Carlo simulations based on a stochastic drug model to test various assumptions and scenarios. 22,23 In the current assessment, the structural PK model parameters and associated variability estimates were used to simulate plasma concentration vs time profiles in 1000 hypothetical subjects at each of the following doses: 800 mg BID, 1200 mg BID, 1600 mg BID, and 1200 mg 3 times daily (TID). At each dose level, the distribution of individual trough JTK-853 concentrations (ie, at 24, 48, and 72 hours) were categorized based on EC 90 multiples (<1, ࣙ1, 1 to <2, 2 to <3, and ࣙ3), and the percentage of subjects in each category was computed.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…Selecting an optimal dosing regimen for new molecular entities is pivotal in the demonstration of positive benefit‐to‐risk balance, and, in turn, to drug approval. For drugs having a wide therapeutic margin, a single available dose (flat dosing) may be safe and effective even without regard to dose adjustments in special populations despite pharmacokinetic (PK) variability resulting from intrinsic and extrinsic factors . However, for drugs with narrow therapeutic indices, flat dosing generally does not provide the optimal benefit‐to‐risk ratio across subjects in the target population.…”
mentioning
confidence: 99%
“…For drugs having a wide therapeutic margin, a single available dose (flat dosing) may be safe and effective even without regard to dose adjustments in special populations despite pharmacokinetic (PK) variability resulting from intrinsic and extrinsic factors. [1][2][3][4] However, for drugs with narrow therapeutic indices, flat dosing generally does not provide the optimal benefit-to-risk ratio across subjects in the target population. In such cases, dose titration algorithms may be needed to achieve a desirable benefit-to-risk balance.…”
mentioning
confidence: 99%